Flipbook-based hybrid media in e-learning Pancasila education course at PGRI Yogyakarta University - Perdana, Oktana Wahyu; Murdiono, Mukhamad; Nurgiansah, T Heru (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The purpose of this research is to (1) develop a hybrid flipbook-based media in e-learning Pancasila Education courses as a step to reduce the use of internet quotas, (2) make Pancasila Education lectures varied and fun, and (3) know the validity of media, matrials, and design. The methods used use a quantitative epproach with this type of research development of the ADDIE model. The research subject of student in semester 1 of Program Studi Pendidikan Pancasila dan Kewarganegaraan of Universitas Negeri Yogyakarta. Data Collection techniques use observationsm interviews, and questionnaires. Data analysis techniques use quantitative descriptive. The results of flipbook-based media research in e-learning Pancasila Education courses at Universitas PGRI Yogyakarta to be used to obtain 87% media validity, 86% material validity, and 88% design validity.  Hybrid media-based flipbook Pancasila Education courses become a variety of fun lectures in the covid-19 pancemic and can reduce the use of the internet because it is used offline. In addition, the use of flipbook-based hybrid media can increase student learning achievement by up to 11%.